2006
DOI: 10.1093/bja/ael084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative i.v. acetaminophen vs i.m. meperidine on post-tonsillectomy pain in children

Abstract: Compared with i.m. meperidine, i.v. acetaminophen provided adequate analgesia, less sedation and earlier readiness for recovery room discharge among paediatric patients undergoing tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 20 publications
1
66
3
1
Order By: Relevance
“…Although multiple studies [18][19][20] have shown an opioid-sparing effect or enhanced analgesic efficacy of intravenous acetaminophen in the adult and pediatric population for various surgical procedures, a similar effect was not seen in our study cohort. One explanation is that our usual analgesic regimen for such patients included an intraoperative dose of morphine (0.1 mg/kg), which was adequate for many of the patients, thereby mitigating the ability to see any additional effect from a single intraoperative dose of a non-opioid analgesic.…”
Section: Discussioncontrasting
confidence: 69%
“…Although multiple studies [18][19][20] have shown an opioid-sparing effect or enhanced analgesic efficacy of intravenous acetaminophen in the adult and pediatric population for various surgical procedures, a similar effect was not seen in our study cohort. One explanation is that our usual analgesic regimen for such patients included an intraoperative dose of morphine (0.1 mg/kg), which was adequate for many of the patients, thereby mitigating the ability to see any additional effect from a single intraoperative dose of a non-opioid analgesic.…”
Section: Discussioncontrasting
confidence: 69%
“…[19,20] A systematic meta-analysis has revealed that IV acetaminophen reduces nausea when prophylactically administered either before surgery or before arrival in the post-anesthesia care unit; but not when administered after the onset of pain. [15] Consistent with these results; the incidence of nausea and vomiting during the first 0-6 h postoperatively was found to be lower in patients who received preoperative paracetamol than in those who received postoperative paracetamol in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The Objective Pain Scale is a validated tool that has been extensively used to compare different analgesic modalities in children (Table 1). 11 In addition, on Day 1 and Day 5, the child completed a modified Faces Scale, a validated tool (ages 1-14 years), which is also commonly used for pain measurement after adenotonsillectomy. 12 Parents were trained by the research staff on how to complete both pain scales.…”
Section: After Approval By Mcmastermentioning
confidence: 99%